"Your Child Has Cerebral Palsy": Parental Understanding and Misconceptions. (July 2021) - Mohanty, Mugdha; Beaulieu, Forrest; Sampath, Spoorthi; Tambunan, Dimira; Kataria, Shivangi; Rosman, N. Paul
Importance: Caregivers of children with cerebral palsy can best help their child if they understand the disorder and the correct terminology. Objective: To assess caregiver understanding of cerebral palsy. Design: This was a cross-sectional study from a large tertiary medical center in Boston, to assess understanding of the term cerebral palsy by primary caregivers of children and adolescents with cerebral palsy. All cases were obtained from hospital electronic medical records. Telephone surveys were conducted. Caregiver understanding of cerebral palsy was assessed by open-ended responses (50%) and success in answering true/false questions about cerebral palsy (50%). Participants: Primary caregivers of children 18 years and younger with cerebral palsy. Results: Thirty-three percent of caregivers denied ever being told that their child had cerebral palsy. Most caregivers identified cerebral palsy as a brain problem (79%), lifelong condition (73%), often caused by a perinatal (60%) or gestational (40%) insult. Fifty-two percent knew that cerebral palsy was nonprogressive. Sixty-two percent of caregivers believed they had a good, very good, or excellent understanding of cerebral palsy, whereas the investigators found 69% of caregivers had a good, very good, or excellent understanding of cerebral palsy (P = .006). Most caregivers rated very good or excellent the setting where cerebral palsy was discussed (58%), the explanations provided (55%), and the amount of time spent (45%), yet using a Pearson correlation coefficient, most important was the time spent ( r = 0.53). Conclusions: Following discussion with their child's physician, most primary caregivers of children with cerebral palsy have a good, very good, or excellent understanding of cerebral palsy. Most critical to a good understanding of cerebral palsy was the time spent in explaining the diagnosis.